2017
DOI: 10.1109/rbme.2017.2757899
|View full text |Cite
|
Sign up to set email alerts
|

Medical Devices for Pediatric Apnea Monitoring and Therapy: Past and New Trends

Abstract: Apnea in the pediatric population is associated with increased morbidity and mortality in a large number of developed as well as developing countries. It is even more prominent in preterm newborn infants and is commonly referred to as apnea of prematurity. Its current diagnosis and therapy involve the use of traditional technologies, which often result in discomfort to the infants due to the use of invasive devices attached to their sensitive skin, especially in overnight clinical sleep analysis (for over a 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…where C L is the load capacitance of each delay cell, I d is the inverter current and V 0 is output voltage swing, which is 1.2 V for 130 nm CMOS process. The current flowing through the transistors is controlled by the gate voltage, V C1 of the transistors, M 1 and M 2 and which on the other hand changes the delay of each delay cells, as shown in (1). When the voltage, V Notch , is low, the M 1 transistor is turned on and the M 2 transistor is turned off and thus the current, I d charges the capacitor, C p .…”
Section: Design Architecture and Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where C L is the load capacitance of each delay cell, I d is the inverter current and V 0 is output voltage swing, which is 1.2 V for 130 nm CMOS process. The current flowing through the transistors is controlled by the gate voltage, V C1 of the transistors, M 1 and M 2 and which on the other hand changes the delay of each delay cells, as shown in (1). When the voltage, V Notch , is low, the M 1 transistor is turned on and the M 2 transistor is turned off and thus the current, I d charges the capacitor, C p .…”
Section: Design Architecture and Simulation Resultsmentioning
confidence: 99%
“…The modern paradigm of wearable devices found a major role in the development of healthcare applications. The detection of respiration pattern represents a topic of interest, especially for preterm infants, in which the use of an invasive device is a limiting factor [1]. In this context, previous investigations have been focused on the fabrication of an integrated device for apnoea detection in preterm infants [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…IBIs, R-R intervals, and changes in movement patterns are the main input features previously used to predict apnoeic events, and are physiological measures routinely monitored in preterm infants admitted to the NICU ( 14 , 15 ). Other potential input features, such as electroencephalography and electromyography, have yet to be explored for their discriminative values as input features in prediction of apnoeic events in preterm infants ( 33 , 34 ). Additionally, no studies have reported the application of clinical information (i.e., caffeine dosage, gestational age, etc.)…”
Section: Current Gapsmentioning
confidence: 99%
“…Respiration monitoring based on Chest Impedance (CI) currently used in NICUs presents limitations when detecting apneas, in particular, cardiac artifacts are a common cause of missed apnea de-tection [24], moreover, motion artifacts and other thoracic movements can also be misinterpreted as respiration [7]. Apneas are strictly defined as a Cessation Of Breathing (COB) longer than 20 seconds or a COB of 10 seconds accompanied by bradycardia and/or desaturation [28]. However, discussions on the definition of clinically relevant apneas move the focus also on shorter COB [13].…”
Section: Introductionmentioning
confidence: 99%